1996
DOI: 10.1016/0014-5793(96)00459-0
|View full text |Cite
|
Sign up to set email alerts
|

The cloning, expression and crystallisation of a thermostable arginase

Abstract: The gene for the thermostable arginase from the thermophilic bacterium 'Bacillus caldovelox" has been cloned and sequenced. Expression of recombinant arginase at high levels has been achieved in E. coil using an inducible T7 RNA polymerasebased system. A facile purification procedure incorporating a heat-treatment step yielded 0.2 g of recombinant arginase per litre of induced culture. The kinetic properties of the purified recombinant protein are essentially identical to the native enzyme. The recombinant pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The addition of Mn 2+ increased enzyme activity by eightfold. This result agreed well with results from most organisms, such as human liver , B. caldovelox , and B. thuringiensis . It is reported that the active site of l ‐arginase contains two Mn 2+ ions (Mn 2+ A and Mn 2+ B ), which are coordinated by Asp and His residues .…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The addition of Mn 2+ increased enzyme activity by eightfold. This result agreed well with results from most organisms, such as human liver , B. caldovelox , and B. thuringiensis . It is reported that the active site of l ‐arginase contains two Mn 2+ ions (Mn 2+ A and Mn 2+ B ), which are coordinated by Asp and His residues .…”
Section: Resultssupporting
confidence: 90%
“…The alignment was performed using DNAMAN 7 program. G. thermodenitrificans arginase had the highest homologous (95.6% identity) and the lowest homologous (22.6% identity) in amino acid sequence with arginase from Bacillus caldovelox DSM411 and Helicobacter pylori B8 , respectively. In addition, ABO65532 exhibited 73.6%, and 69.0% amino acid sequence similarities with arginase from Bacillus anthracis BFV and B. subtilis 168 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The metal cluster is located in a 15 Å deep cleft with the Mn 2+ atoms 3.3 Å apart and bridged by a solvent molecule [35]. Structures from the bacteria Bacillus caldovelox [36,37], human arginase I [38] and II [39], rat arginase I [35,40] and Thermus thermophilus [Protein Data Bank (PDB) codes: 2EF4, 2EF5 and 2EIV] have been determined. In the mechanism proposed by Kanyo et al.…”
mentioning
confidence: 99%